2014
DOI: 10.1097/qai.0000000000000340
|View full text |Cite
|
Sign up to set email alerts
|

Depot-Medroxyprogesterone Acetate Does Not Reduce the Prophylactic Efficacy of Emtricitabine and Tenofovir Disoproxil Fumarate in Macaques

Abstract: Concerns that the injectable contraceptive depot-medroxyprogesterone acetate (DMPA) may increase the risk of HIV acquisition in women led to questions on whether DMPA could reduce efficacy of pre-exposure prophylaxis (PrEP) for HIV prevention. We used a macaque model to investigate the impact of prolonged DMPA on PrEP with FTC/TDF. Twelve pigtail macaques treated with DMPA were exposed vaginally to SHIV once a week for up to 5 months and received either placebo (n=6) or FTC/TDF (n=6). All control macaques were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
4
17
0
Order By: Relevance
“…(21, 47, 48) Pigtails can also be easily infected vaginally with low virus doses without the use of exogenous progestins such as depot-medroxyprogesterone acetate (DMPA). (21, 47, 49, 50) While treatment of rhesus macaques with high DMPA doses also ensures vaginal infection at lower virus doses, this DMPA dose does not fully reproduce the biological effects of DMPA seen in women. (50)…”
Section: Animal Model Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…(21, 47, 48) Pigtails can also be easily infected vaginally with low virus doses without the use of exogenous progestins such as depot-medroxyprogesterone acetate (DMPA). (21, 47, 49, 50) While treatment of rhesus macaques with high DMPA doses also ensures vaginal infection at lower virus doses, this DMPA dose does not fully reproduce the biological effects of DMPA seen in women. (50)…”
Section: Animal Model Supportmentioning
confidence: 99%
“…. (21, 49, 50) The high protection seen with DMPA was reassuring since DMPA is the most commonly used method of contraception in sub-Saharan Africa and has been associated with higher risk of HIV infection in some studies. (51, 52) Assessing the same PrEP modaltity in macaques co-infected with Chlamydia trachomatis and Trichonomas vaginalis also found protection although infection in some animals signaled a modest loss of PrEP activity due to these two STIs.…”
Section: Animal Model Supportmentioning
confidence: 99%
“…[60][61][62] Many studies have focused on the histology of the vaginal wall in PTM and RM. 2,33,38,45,47,48,56,63 RM vaginal tissues are reportedly more keratinized than those of PTM, 38,45,64 and the degree of keratinization varies with phase of menstrual cycle. 45,56,63 A common feature of humans, RM, and PTM is that all exhibit thinning of vaginal epithelium during the luteal phase, although the extent may vary among species (Fig.…”
Section: Types Of Non-human Primate Models For Studying How Hormonal mentioning
confidence: 99%
“…In PTM, we have shown that a desogestrel and ethinyl estradiol combined oral contraceptive (administered orally) suppress progesterone and estradiol. 40 MPA, given by injection, also suppresses progesterone and estradiol in PTM 47,48 (and E. Kersh, unpublished observations). Finding the human-equivalent dose of exogenous hormones requires extensive pharmacokinetic and pharmacodynamic studies over several months, using a combination of measures including levels of proges- terone and estradiol and vaginal thinning.…”
Section: Types Of Non-human Primate Models For Studying How Hormonal mentioning
confidence: 99%
See 1 more Smart Citation